Keseimbangan Pasar Barang dalam Perpektif Ekonomi - Susanti, Novi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The equilibrium of the commodity market in Islamic economics is based on the principles of justice, transparency, and compliance with sharia law. In this perspective, the market is not only seen as a balancing mechanism between supply and demand, but also as a means of ensuring a fair distribution of wealth and maintaining social welfare. This article explains the concept of market equilibrium in Islam, which differs from conventional economic systems by emphasizing business ethics, prohibition of usury, gharar (speculation), as well as monopoly practices. In addition, government intervention in Islamic economics aims to prevent market distortions and protect the rights of consumers as well as producers. The study also discusses the role of regulatory agencies such as the SEC in maintaining market integrity. Through this analysis, it is hoped to provide an in-depth understanding of how commodity market equilibrium is applied in the framework of Islamic economics, as well as its relevance in modern economic systems.